Teachers’ Digital Competency Transformation through Sparkol Videoscribe: Technical, Pedagogical, and Identity Shifts in Madrasah Tsanawiyah - Hamdi Abdul Karim; Helfi Helfi; Fadhil Hardiansyah; Siska Oktavia; Gusnia Darniati; Resa Afri Yuliandri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The rapid development of digital technology necessitates new teacher competencies, yet how educators transform through specific tools in resource-limited contexts remains underexplored. Grounded in the DigComp framework and multimedia learning theory, this qualitative intrinsic case study examines the digital competency transformation of Madrasah Tsanawiyah (MTs) teachers using Sparkol Videoscribe animation media. Data from interviews, observations, and documentation involving six teachers in Agam Regency, West Sumatra were analyzed thematically. Findings reveal a significant three-dimensional transformation: (1) technical competence evolved from basic digital literacy to productive content creation; (2) pedagogical practice shifted from lecture-based instruction to interactive, multimodal, student-centered learning; and (3) professional identity was reshaped by a growth mindset, heightened self-efficacy, and proactive technology exploration. Despite challenges like limited devices and internet access, teachers developed adaptive strategies including peer collaboration and personal content banks. Theoretically, this study contributes to teacher professional development literature by demonstrating how experiential tool-based learning fosters holistic competency growth. Practically, it underscores the need for institutional policies that provide technological infrastructure, foster collaborative communities of practice, and integrate hands-on digital media training into sustainable professional development programs for madrasah teachers.